Comparison of Long-Term Memory function in Elderly across Mind Activity and Diabetes Mellitus-Type 2 - Sara Shabani; Sudeh Shabani; Mohsen Dehghani; Mojtaba Habibi (Journal of Behavior Therapy And Mental Health, 2016)
Objectives: While Diabetes Mellitus (DM) affects cognitive functions and the Long Term Memory (LTM), several different strategies are designed to control harmful consequences of DM. This study is investigating whether having Mind Activity (MA) can make any difference in LTM function of individuals with DM. Design: The participants (n=80) were classified in 4 groups based on having DM or not and having MA or not. Methods: The LTM and MA were assessed respectively by the word-list of Tulving and Pearlstone, and a self-report form. The BG concentrations were measured in vitro. Results: The results showed a significant negative correlation between BG concentrations and LTM scores in group with DM. The LTM function is significantly lower in group with DM and no-Mind Activity (nMA) respectively than the group with no-Diabetes Mellitus (nDM) and with MA. Also the LTM scores of the groups with nDM&MA, nDM&MA, DM&MA, nDM&MA, nDM&nMA and nDM&MA which were respectively higher than those of the groups with nDM&nMA, DM&MA, DM&nMA, DM&nMA, DM&nMA and DM&MA were statistically significant. Conclusions: The weaker BG control in patients with DM, the higher LTM dysfunction; and LTM function is in close relationship with DM (negatively) and MA (positively). Patients with DM and individuals with nDM who have their minds active in elderly, may less likely confront LTM dysfunction than matched groups who do not have active minds.
Keywords: Diabetes mellitus-type 2